The storyteller - James Danielsen (Internet Policy Review)
This story is inspired by the growing feasibility of Decentralised Autonomous Corporations (DACs), operating by means of distributed blockchain technologies. The story is set in the near future where a decentralised corporation – powered by machine-learning algorithms and fed on an unending stream of data – has entirely penetrated the fabric of society. Ultimately, however, it is the narcissism of humans – their insatiable need to be recognised in some way – that drives the exponential power of the corporation. Some of the themes that emerge from the story are: 1) the production of social media content, 2) the dangers of corporate personhood, 3) the nature of human and non-human agency, 4) the nature of truth in the context of the information age, and 5) the potential impact of fully autonomous technologies.